The impact of brand awareness, green marketing, and consumer behaviour on purchasing decisions: Empirical evidence from Bottled Water consumers in South Jakarta - Ridoan, Ahmad; Rochman, Abdul; Maftuchach, Viniyati (Journal of Economics and Business Letters, 2025)
The bottled water industry in Indonesia is experiencing rapid growth and increasingly fierce competition, in line with the growing public demand for hygienic and practical products. Additionally, consumer awareness of environmental and sustainability issues also influences purchasing preferences. However, there is a limited amount of empirical research that simultaneously examines the influence of brand awareness, green marketing, and consumer behaviour on purchasing decisions, particularly for AMDK products in urban areas. This study aims to analyse the influence of these three variables on purchasing decisions for Aqua products in South Jakarta. This study employs a quantitative approach using a survey method targeting 160 Aqua consumers selected through purposive sampling. Data were collected via questionnaires and analysed using validity and reliability tests, as well as multiple linear regression.The results indicate that brand awareness has the most significant influence on purchasing decisions, followed by green marketing and consumer behaviour. The research model explains 85.8% of the variation in purchasing decisions. The limitations of this study lie in its geographical scope and limited sample size, meaning the results cannot be generalised nationally.The main contribution of this study is to provide new empirical evidence regarding the integration of the three main variables in the context of the Indonesian bottled water industry, as well as offering practical recommendations for companies to strengthen their sustainability-based marketing strategies and brand reinforcement.